Makkaḷ kaviñar Pārati - Celvam, Kō., 1932- (Cantāṉam Patippakam, 1982)
Comparative study of the poetry of Pāratiyār, 1882-1921, Tamil litterateur and Indian freedom fighter, and Vladimir Mayakovsky, 1894-1930, Russian poet.